Arts and technology : fourth International Conference, ArtsIT 2014, Istanbul, Turkey, November 10-12, 2014, Revised selected papers /: fourth International Conference, ArtsIT 2014, Istanbul, Turkey, November 10-12, 2014, Revised selected papers. (2015) - Unknown
No abstract available